Prognostic impact of Skp2, ER and PGR in male and female patients with soft tissue sarcomas - Sorbye, Sveinung W (BioMed Central, 2013)
BACKGROUND: S-phase kinase-associated protein 2 (Skp2) is a member of mammalian F-box proteins. The purpose of this study is to clarify the prognostic significance of expression of Skp2 related to gender, estrogen receptor (ER) and progesterone receptor (PGR) in soft tissue sarcomas (STS). Skp2 has been demonstrated to display an oncogenic function since its overexpression has been observed in many human cancers. Optimized treatment of STS requires better identification of high-risk patients who will benefit from adjuvant therapy. The prognostic significance of Skp2 related to ER and PGR in STS has not been sufficiently investigated. METHODS: Tissue microarrays from 193 STS patients were constructed from duplicate cores of viable and representative neoplastic tumor areas. Immunohistochemistry was used to evaluate the expression of Skp2, ER and PGR. RESULTS: In univariate analyses, high tumor expression of Skp2 correlated (p = 0.050) with reduced disease-specific survival (DSS). In subgroup analyses expression of PGR in males (p = 0.010) and in patients older than 60 years (p = 0.043) were negative prognostic factors for DSS. Expression of ER in females was a positive prognostic factor for DSS (p = 0.041). In co-expression analyses in the whole cohort, low expression of Skp2 in combination with low expression of ER was positive for DSS (p = 0.049). In females high expression of Skp2 in combination with low expression of ER was a negative prognosticator (p = 0.021). In the multivariate analyses, age (p = 0.012), malignancy grade (p < 0.001), wide resection margins (P = 0.010), ER negative / PGR positive co-expression profile (p = 0.002) and ER positive / PGR negative co-expression profile (p = 0.015) were independent negative prognostic factors for DSS. In females expression of Skp2 (p = 0.006) was associated with shorter DSS. CONCLUSIONS: We found diverse prognostic impacts of expression of Skp2, ER, PGR and DSS in male and female patients with STS. In men, but not women, ER positive / PGR negative co-expression profile was an independent negative prognostic factor for DSS. In women, but not men, high expression of Skp2 was associated with reduced DSS.